Am I fine? Exploring everyday life ambiguities and potentialities of embodied sensations in a Danish middle-class community (Medicine Anthropology Theory, 2020)
Woven into the fabric of human existence is the possibility of death and suffering from disease. This essential vulnerability calls forth processes of meaning making, of grappling with uncertainty and morality. In this article we explore the uncertainty and ambiguity that exists in the space between bodily sensations and symptoms of illness. Bodily sensations have the potential to become symptoms of disease or to be absorbed into ordinariness, prompting the question: how do we ascribe meaning to sensations? In the context of middle-class everyday life in Denmark, we show how different potentialities of ambiguous sensations are weighed against each other on a culturally and morally contingent continuum between normal and not normal, uncovering the complex interplay between the body, everyday life, and pervasive biomedical discourses focusing on health promotion, symptom awareness, and care seeking.